Combination treatment with secukinumab and dimethyl fumarate in a patient with psoriasis and recent diagnosis of multiple sclerosis. Issue 6 (14th July 2020) - Di Tullio, Francesca; Odorici, Giulia; Lasagni, Claudia; Capobianco, Marco; Conti, Andrea; Mandel, Victor Desmond
Abstract: The therapeutic approach to patients with psoriasis and concomitant multiple sclerosis is challenging. We report the clinical case of a 44‐year‐old man affected by psoriasis and psoriatic arthritis treated with secukinumab for 2 years, who received also dimethyl fumarate because of a recent diagnosis of relapsing remitting multiple sclerosis. Moreover, a mini‐review of the available literature regarding the use of secukinumab in patients with psoriasis or ankylosing spondylitis and coexisting central nervous system demyelinating diseases was performed. To the best of our knowledge, this is the first case of successfully combining secukinumab and dimethyl fumarate for the treatment of two different immune mediated inflammatory diseases with good response and safety outcomes. Our case emphasizes the potential efficacy of this combination therapy, which may represent an effective synergistic strategy to manage such challenging patients.